Peningkatan Kapasitas Promosi Digital pada UMKM Wisata Kuliner Cafe Sawah Glagahwero melalui Pendampingan dan Implementasi Branding - Fawaid Fawaid; Saini Saini; Muhammad Ali Zainur Ridho; Dwi Rafelika Angger Adinata; Riksen Riksen; Muhammad Alfa Hasim; Muhammad Naufal Febriansyah; Ahmad Danial Sahwan; Mohammad Ali Imron; Ikmalul Khoir; M. Fiqi Zulqornain (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the digital promotional capacity of Cafe Sawah Glagahwero's culinary tourism through mentoring and implementing branding strategies. Cafe Sawah is a village asset managed by a Village-Owned Enterprise (BUMDes) with significant potential to support nature-based tourism but is hampered by limited digital literacy and suboptimal promotional strategies. The Asset-Based Community Development (ABCD) method was used, encompassing observation, branding strategy design, digital content creation assistance, promotional implementation, and monitoring and evaluation. The mentoring results demonstrate improved management skills in photography, videography, content editing, and social media management. The branding implementation resulted in a consistent visual identity, an increase in the number of Instagram followers from 0 to 360 with a 7.8% engagement rate, and an increase in customer visits. These findings confirm that the synergy between human resource capacity building and digital promotional efforts can strengthen brand image, increase competitiveness, and provide sustainable economic benefits for the village community. This program is expected to become a model for developing other village assets utilizing digital technology and branding strategies.